The relationship of occupational injury and use of mental health care. (September 2020) - López Gómez, María Andrée; Williams, Jessica A.R.; Boden, Leslie; Sorensen, Glorian; Hopcia, Karen; Hashimoto, Dean; Sabbath, Erika
Highlights: A matched cohort study assessing occupational injury and use of mental health care. Injured workers were more likely to seek mental health care services post-injury. Lower wage workers had a higher likelihood to seek mental health care post-injury. Abstract: Introduction: Symptoms of depression and anxiety are a common consequence of occupational injury regardless of its cause and type. Nevertheless, mental health care is rarely covered by workers' compensation systems. The aim of this study was to assess the use of mental health care post-injury. Methods: We used a subsample of patient-care workers from the Boston Hospital Workers Health Study (BHWHS). We matched one injured worker with three uninjured workers during the period of 2012–2014 based on age and job title (nurse or patient-care associate) and looked at their mental health care use pre- and post-injury using medical claims data from the employer sponsored health plan. We used logistic regression analysis to assess the likelihood of mental health care use three and six months post-injury controlling for any pre-injury visits. Analyses were repeated separately by job title. Results: There were 556 injured workers between 2012 and 2014 that were matched with three uninjured workers at the time of injury ( n = 1, 649). Injured workers had a higher likelihood of seeking mental health care services than their uninjured counterparts during the six months after injury (OR = 1.646, 95% CI: 1.23–2.20), but not three months post-injury (OR = 0.825, 95% CI: 0.57–1.19). Patient-care associates had a higher likelihood to seek mental health care post-injury, than nurses (OR: 2.133 vs OR: 1.556) during the six months period. Conclusions: Injured workers have a higher likelihood to experience symptoms of depression and anxiety based on their use of mental health care post-injury and use is more predominant among patient-care associates; however, our sample has a small number of patient-care associates. Practical Applications: Treating depression and anxiety as part of the workers' compensation system has the potential of preventing further physical ailment and improving the return to work process regardless of nature of injury.